Nasal Duplication Combined with Cleft Lip and Palate: Surgical Correction and Long-Term Follow-Up - Long, Kanharith (Plast Reconstr Surg Glob Open, 2017)
BACKGROUND: Diprosopus dirrhinus, or nasal duplication, is a rare entity of partial craniofacial duplication. METHODS: The case we present is the first report of diprosopus dirrhinus associated with complete cleft lip and palate. The baby was born in Cambodia at full term by normal vaginal delivery with no significant perinatal and family history. Physical examination revealed significant facial deformity due to the duplicated nose and the left complete cleft lip/palate on the right subset. RESULTS: There were 4 nostrils; both medial apertures including the cleft site were found to be 10–15 mm deep cul-de-sac structures without communication to the nasopharynx. The upper third of the face was notable for hypertelorism with a duplication of the soft-tissue nasion and glabella. Between the 2 nasal dorsums, there was a small cutaneous depression with a lacrimal fistula in the midline. Surgical treatment included the first stage of primary lip and nose repair and the second stage of palatoplasty. CONCLUSIONS: The patient was followed up at the age of 10 years showing satisfactory results for both aesthetic and functional aspects. Further management in the future will be required for the hypertelorism and nasal deformity.